Investigation of Radon, Total Electron Content and Linear and Nonlinear Variations of Meteorological Variables Due to Earthquakes: ARIMA and Monte Carlo Modelling - Mohammed, Marjan; Salh, Hemn; Külahcı, Fatih (My University, 2024)
An Integrated Autoregressive Moving Average (ARIMA) - Monte Carlo Simulation (MCS) is proposed to analyze and model the anomalies of atmospheric and ground gases by an earthquake along the North Anatolian Fault Zone (Türkiye). Earthquakes, Soil radon gas and Total Electron Content (TEC) showed simultaneous anomalies. There are positive relationships between these three parameters. Also, positive relations between Rn, meteorology, and atmosphere are detected. The proposed ARIMA model and MCS for the Rn-TEC-Earthquake relationships of the measured data gave statistically significant results. This model and simulation showed statistically significant changes in the effects of microearthquakes, which are more difficult to detect than large earthquakes, especially on the ionospheric TEC.
Keywords: ARIMA; Monte Carlo Simulation; Total Electron Content; Earthquake precursors